Medium-term growth-at-risk in the euro area - Jan Hannes Lang; Marek Rusnák; Moritz Greiwe (European Central Bank (ECB), 2023)
Financial stability indicators can be grouped into financial stress indicators that reflect heightened spreads and market volatility, and financial vulnerability indicators that reflect credit and asset price imbalances. Based on a panel of euro area countries, we show that both types of indicators contain information about downside risks to real GDP growth (growth-at-risk) in the short-term (1-year ahead). However, only vulnerability indicators contain information about growth-at-risk in the medium-term (3-years ahead and beyond). Among various vulnerability indicators suggested in the literature, the Systemic Risk Indicator (SRI) proposed by Lang et al. (2019) outperforms in terms of in-sample explanatory power and out-of-sample predictive ability for medium-term growth-at-risk in euro area countries. Shocks to the SRI induce a rich "term structure" for growth-at-risk: downside risks to real GDP growth are reduced in the short-term, but over the medium-term the effect reverses and downside risks to real GDP growth go up considerably. We also show that using cross-country information from the panel of euro area countries can improve the out-of-sample forecasting performance of growth-at-risk for the euro area aggregate.
Keywords: E37; E44; G01; G17; C22; 330; Growth-at-risk; financial stress; financial vulnerabilities; quantile regression; local projections